Influence of annealing on the physical and optical properties of Ge thin films deposited using thermal evaporation - Hilmi, Isom; Adam, Muhammad Kevin; Purwadi, Joko; Soesanto, Qidir Maulana Binu; Kusuma, Damar Yoga (Diponegoro University Semarang Indonesia, 2025)
Germanium (Ge) is extensively utilized in various technological applications, particularly in optoelectronic devices due to its favorable electronic properties. In this study, Ge thin films were deposited onto soda-lime glass substrates using the thermal evaporation technique. The deposited films were subsequently subjected to annealing at temperatures ranging from 200 to 700 °C. Comprehensive characterization of the films was performed using XRD to analyze crystallinity, UV-Vis spectroscopy to evaluate optical properties, and SEM to investigate surface topography. The annealing process induced a significant phase transformation from an amorphous state to a co-existing Ge and GeO2 structures, as evidenced by XRD measurements. This structural evolution was accompanied by notable changes in the optical properties of the films. Specifically, an increase in annealing temperature resulted in a higher absorbance in the longer wavelength regions of the UV-Vis spectrum. These findings highlight the possibility of a controlled manipulation on the structural and optical characteristics of Ge thin films by thermal treatment, with potential applications in optoelectronic devices.